Pengaruh Mirror Theraphy terhadap Peningkatan Kekuatan Otot pada Penderita Stroke - Neneng Hasanah; Zahrah Maulidia Septimar (Jurnal Health Sains, 2021)
The World Health Organization (WHO) Data shows that deaths of 7.9% of all deaths occurring in Indonesia are caused by stroke. According to the data obtained in RSU Kabupaten Tangerang, there are 208 patients suffering from stroke and treatment in hospital period from March to May 2020. In patients with stroke will usually experience weakness in muscles based on some research gained that one of the complementary therapies that can be performed in a non-hemorrhagic stroke patients is mirror therapy. Mirror Therapy is the shape motoric imagination that is expectable visual, mental performance of a movement without doing the movement. The study aims to collect and analyze articles related to the intervention of increasing the muscle strength of the stroke sufferers with Mirror Therapy. The design used is the Literature Review, articles gathered by using the search engine Google Scholar, PUBMED, Medline and Resarchgate. The article criteria used were published in 2014-2020. Based on the article collected the results that Mirror Therapy proved to improve muscle strength in Stroke patients. Mirror Therapy can also be combined with other therapies such as ROMS, acupresure, and motivation support against Stroke patients. The role of nurses in giving therapy and support to patients is also very influential. Mirror Therapy will be more effective in enhancing muscle strength in stroke patients when done routinely and disciplined.